Cardiac complications of malnutrition in adolescent patients: A narrative review of contemporary literature - JosephBurns; CarolineShank; MadhusudanGanigara; NadiaSaldanha; ArushiDhar (Wolters Kluwer Medknow Publications, 2021)
Eating disorders are common. Between 1% and 2% of adolescent females and 0.5% of males suffer from anorexia nervosa, bulimia nervosa, and binge eating disorder. Although suicide represents nearly half of the mortality in patients with eating disorders, a majority of the remainder is cardiac arrest, likely secondary to cardiovascular complications of eating disorders such as bradycardia, hypotension, QT interval changes, structural heart disease, and pericardial effusion. Bradycardia is suspected to be secondary to increased vagal tone and is a common finding in patients admitted with disordered eating. Similarly, hypotension and orthostatic abnormalities are common complications due to atrophy of peripheral muscles. Descriptive studies report prolongation of the corrected QT interval (QTc) in these patients relative to controls, albeit within the normal reference range. Structural heart disease is also common, with left ventricular mass reported as lower than predicted in several studies compared to healthy controls. Pericardial effusion is also commonly described, although it is possible that this is underestimated, as not all patients with eating disorders undergo echocardiograms. Further, refeeding syndrome as a result of treatment of eating disorders carries its own cardiac risks. Cardiac complications of malnutrition are common but reversible with appropriate management and recovery. It is imperative that providers are aware of the epidemiology of these complications, as it is only with a high clinical suspicion that proper evaluation including a thorough history and physical examination, electrocardiogram, and when necessary echocardiogram can be performed.